2014
DOI: 10.4314/ajcem.v16i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cytomegalovirus Infection amongst Pregnant Women in Kaduna State, Nigeria

Abstract: Cytomegalovirus (CMV) is a major public health problem throughout the world. It is the leading cause of congenital infections leading to neurological disabilities in children that result to severe sequelae such as sensor neural hearing loss, neuro-developmental delay and blindness. This study was conducted to determine the seroprevalence of human cytomegalovirus among pregnant women in Kaduna State, Nigeria. Three hundred and sixty three (363) blood samples were collected from 330 pregnant women attending ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
10
16
1
Order By: Relevance
“…However, there was statistical association between seronegativity with education level and history of previous blood transfusion. These findings are in consonance with previous studies (Hamdan et al, 2011;Matos et al, 2010;Yeroh et al, 2015;Akinbami et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…However, there was statistical association between seronegativity with education level and history of previous blood transfusion. These findings are in consonance with previous studies (Hamdan et al, 2011;Matos et al, 2010;Yeroh et al, 2015;Akinbami et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The result therefore showed that level of education had no effect on the transmission of CMV infection. This is similar to other studies [6]. Again, the table also depicted the relationship between CMV infection and occupational status.…”
Section: Discussionsupporting
confidence: 75%
“…This means that the CMV viral dose circulating in their blood were not adequate to elicit disease. This discovery of ubiquitous nature of CMV is in consonance with the works of previous researchers that CMV has a worldwide distribution, with prevalence rate of 70%-100% [6,40,57,58]. The reason for this could be attributed to recent infection or reactivation due to diminishing immunity in the immune-compromised individuals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…IgG antibodies may be measurable at low levels for many years and in some cases for a lifetimes [7]. This study revealed a higher ratio of CMV in age group (20)(21)(22)(23)(24)(25), but this results was un agree with [20] that showed that (46.6%) of infection in the age group (15-19 years) with significant differences under Pv=0.01.…”
Section: Discussionsupporting
confidence: 36%